ANALISIS KESULITAN DALAM MENYELESAIKAN SOAL BANGUN RUANG PADA SISWA KELAS V SD INPRES PARE’ PARE’ KEC. BAJENG KAB. GOWA - Nurhayani Juhasan; Mutmainnah; Ernawati (STKIP Subang, 2025)
This study aims to analyze students’ difficulties in solving mathematics problems on the topic of three-dimensional shapes, including difficulties in using concepts, principles, and solving verbal problems. This research uses a descriptive qualitative approach with data collection techniques in the form of tests, interviews, and documentation. The research subjects consisted of 3 students from a total of 22 fifth-grade students at SD Inpres Pare’ Pare’, Bajeng District, Gowa Regency, who were selected based on high, medium, and low levels of mathematical ability. The obtained data were analyzed through the stages of data reduction and drawing conclusions. The results of the study show that difficulties in using concepts were experienced by students with both high and low abilities. High-ability students had difficulty because they forgot formulas. Meanwhile, low-ability students showed a deep lack of understanding of basic concepts of three-dimensional shapes, such as formulas for volume and surface area. Difficulties in using principles were experienced by students with medium and low abilities. They often made errors in calculations, used incorrect formulas, or did not complete the problem-solving process correctly. This indicates a weak mastery of basic mathematical principles. Difficulties in solving verbal problems were experienced by students with medium and low abilities. These students had difficulty understanding word problems, identifying relevant information, and formulating solution strategies. The main cause was the inability to relate contextual information to mathematical form.